A Panel Data Analysis on China's Intra-Industry Trade in the Capital Goods Sector - Yiping Zhu (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2009)
This paper adopts the Hausman-Taylor 2SLS error components approach in estimating the determinants of China's Intra-Industry Trade (IIT) in the capital goods sector with its 26 partner countries. It disaggregates IIT into horizontal IIT (HIIT) and vertical IIT (VIIT). Capital goods final products and intermediates are separately estimated in order to reveal the differentiated trade patterns. It finds that economic similarity is very significantly negatively correlated with the intermediates IIT, but to a less extent correlated with the final products IIT. Factor endowment is of no significance in determining IIT in the intermediates, although it is significantly positively correlated with the final products IIT. Economic size is signi?cantly negatively correlated with both final products and intermediates IIT. Distance is not yet dead in impacting the level of final products IIT, but of less importance in influencing the intermediates IIT. China is exchanging intermediates in a less intraindustry manner with ASEAN nations. However, because VIIT is dominating TIIT, no significant differences exist between the estimation results of TIIT and VIIT. – – Diese Studie verwendet die Methode der Hausman-Taylor-2SLS Fehler-Komponenten zur Schätzung der Determinanten von Chinas Intraindustriellem Handel (IIT) im Investitionsgütersektor mit seinen 26 Partnerländern. Sie disaggregiert IIT in horizontalen IIT (HIIT) und vertikalen IIT (VIIT). Investitionsgüter, Endprodukte und Halbfertigwaren werden separat geschätzt, um die Unterschiede des Handels zu interpretieren. Es zeigt sich, dass die wirtschaftliche Ähnlichkeit mit IIT-Halbfertigwaren signifikant negativ korreliert ist, aber bei IIT-Endprodukten keine Signifikanz besteht. Der Faktor Ausstattung weist keine Signifikanz bei der Bestimmung von IIT-Halbfertigwaren auf, obwohl er mit IIT-Endprodukten signifikant positiv korreliert ist. Wirtschaftsgröße ist sowohl mit IIT-Endprodukten als auch mit IIT-Halbfertigwaren signifikant negativ korreliert. Entfernung wirkt sich auf das Niveau von IIT-Endprodukten aus, hat aber einen geringeren Einfluss auf IIT-Halbfertigwaren. China hat im Bereich Halbfertigwaren relativ wenig intraindustriellen Handel mit ASEAN-Staaten. Da jedoch VIIT einen dominierenden Einfluss auf TIIT ausübt, bestehen keine bedeutenden Unterschiede zwischen den Schätzungsergebnissen von TIIT und VIIT.
urn:nbn:de:101:1-20091222756
Keywords: F14; C33; 330; Intraindustrieller Handel; Panelökonometrie; Intra-Industry Trade; Panel Econometrics; Intraindustrieller Handel; Investitionsgüterindustrie; Panel; Schätzung; China; Welt